Sleep Quality and Nocturnal Pain in The Patients of Lumbar Disc Herniation : Sleep Quality and Nocturnal Pain - Altaf, Faiza; Ahmad, Danyal; Zahra, Tazeen; Ameen, Zahra; Tanveer, Rimsha; Afzal, Maryam; Batool, Seerat; Khalid, Amna (Pakistan Journal of Health Sciences, 2023)
Patients with lumbar disc herniation frequently report experiencing nocturnal back discomfort that interferes with their ability to sleep adequately. This study’s objective is to describe and evaluate the pain and sleep quality of individuals with disc herniation diagnoses. Objective: To assess sleep quality and nocturnal pain in patients of lumbar disc herniation. Methods: Patients range from 24-65 years, both males and females with positive straight leg raise and prone knee bending test were selected with random sampling technique. Data were collected after filling a comprehensive questionnaire. PSQI questionnaire was used to access quality of sleep disturbance. Visual analog scale was the tool that used to help the person rate the intensity of pain at night. Results: The results showed that 6(12%) had mild disturbance in sleep, 33(66%) had moderate disturbance in sleep and 11(22%) had severe disturbance in sleep according to global PSQI. Conclusions: According to the findings from our study, lumbar disc herniation has negatively impacted the participants’ ability to sleep. Sleep disruption and pain were connected, and nocturnal discomfort affected patient’s activities of daily liv